2014
DOI: 10.1007/s12262-014-1056-z
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Impact: Utility of Reflective Approach in the Practice of Surgery

Abstract: Social media is rapidly being incorporated into medical education. We created a small group, reflective practice sessions by integrating specific medical cases to improve awareness about professionalism on social media. Medical scenarios were generated for reflective practice sessions on social media professionalism. Anonymous pre/post-session surveys evaluated residents' use of social media and gathered their opinions on the session. Thirty-eight of 48 (79 %) residents replied to the presession survey with 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 18 publications
3
9
0
Order By: Relevance
“…Among 88 studies, 49 were quantitative [ 32 , 33 , 35 , 38 - 43 , 51 - 53 , 55 , 59 - 61 , 64 , 66 - 69 , 71 , 72 , 74 , 75 , 77 - 80 , 82 , 85 , 88 , 89 , 91 , 94 - 96 , 98 , 100 , 102 , 105 - 108 , 110 , 113 , 114 , 116 , 118 ], 12 were qualitative [ 34 , 36 , 44 , 45 , 49 , 57 , 73 , 76 , 92 , 93 , 101 , 104 ], and 27 used mixed methods [ 35 , 37 , 46 - 48 , 50 , 54 , 56 , 58 , 62 , 63 , 65 , 70 , 81 , 83 , 84 , 86 , 87 , 90 , 97 , 99 , …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among 88 studies, 49 were quantitative [ 32 , 33 , 35 , 38 - 43 , 51 - 53 , 55 , 59 - 61 , 64 , 66 - 69 , 71 , 72 , 74 , 75 , 77 - 80 , 82 , 85 , 88 , 89 , 91 , 94 - 96 , 98 , 100 , 102 , 105 - 108 , 110 , 113 , 114 , 116 , 118 ], 12 were qualitative [ 34 , 36 , 44 , 45 , 49 , 57 , 73 , 76 , 92 , 93 , 101 , 104 ], and 27 used mixed methods [ 35 , 37 , 46 - 48 , 50 , 54 , 56 , 58 , 62 , 63 , 65 , 70 , 81 , 83 , 84 , 86 , 87 , 90 , 97 , 99 , …”
Section: Resultsmentioning
confidence: 99%
“…Studies that assessed SM use among different types of HCPs found high use among students, from 66.9% to 98.7% [ 40 , 43 , 50 , 51 , 60 , 61 , 64 - 66 , 68 - 70 , 102 ]; the highest with 98.7% using Facebook at least once a week was established among dental students. Lower rates of use were seen in practicing HCPs, physicians of different specialties, and program directors (PDs) or faculty, mostly ranging from 50% to 80% [ 35 , 39 , 74 , 80 , 83 , 85 , 86 , 88 , 89 , 91 , 96 , 105 , 106 , 108 , 110 , 113 , 114 ]. The exceptions were 3 studies: family medicine residents and physicians in Saudi Arabia where 95.4% of participants reported having an SM account and checking them at least once a day [ 79 ], 93.4% of medical doctors in a Singapore hospital [ 100 ], and 100% of Chinese registered nurses owned an SM account [ 107 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From 2014 to 2016, during the CUA Annual National Academic Conference on Minimally Invasive Urology, attendees of the meeting of urological surgeons were invited to complete an anonymous 19-item questionnaire (in 2016, 3 more questions were added to the survey, for 22 questions in total; see S1 Fig ). The questionnaire was piloted by the authors and a separate group of urologists in Hunan Province based on two previous surveys[ 19 , 20 ]. The survey took approximately 10 minutes to complete and queried respondents about their personal and professional use of social media.…”
Section: Methodsmentioning
confidence: 99%